EDUKASI OLAHRAGA UNTUK MENINGKATKAN IMUNITAS TUBUH DALAM MENGHADAPI BENCANA NASIONAL PENYEBARAN COVID19 - Apriyani Apriyani (Khidmah, 2021)
The COVID-19 pandemic in 2020 brought many changes in people's lives. Everything must be done at home. Study, work, worship, even sports are recommended at home. Moderate-intensity exercise, in a well-ventilated environment and alone and avoiding contact with other people (e.g. at home), and prioritizing the use of personal sporting goods are recommended. Home exercise program is one of the sports options because in its implementation it is safe, easy and cheap. This program includes aerobics (eg walking at home or nearby), muscle strength training (strengthening), stretching and balance exercises or a combination. One of the service activities carried out is Sports Education to Improve Body Immunity for the Prevention of Covid -19. This community service activity will be held 09 April 2021 on Jl. Pipa Jaya Kel. 15 Ulu Kec. Jakabaring Keywords: Education, Sports, Body Immunity